ChemInform Abstract: Cyclopropanation of Diazoesters with Styrene Derivatives Catalyzed by Magnetically Recoverable Copper‐Plated Iron Nanoparticles. Issue 3 (January 2015) - Ishikawa, Shingo; Hudson, Reuben; Masnadi, Mitra; Bateman, Mary; Castonguay, Annie; Braidy, Nadi; Moores, Audrey; Li, Chao‐Jun
Abstract The reaction of (I) and aliphatic alkenes other than (IIf), such as hex‐1‐ene, methyl acrylate, and ethenyl acetate, yields the corresponding cyclopropanated products in trace amounts only.